The Impact of Geohazards on Sustainable Development of Rural Mountain Areas in the Upper Reaches of the Min River - He, Yanfen; Ding, Mingtao; Liu, Kang; Lei, Min (Frontiers in Earth Science, 2022)
There is a coupling mechanism among geohazards, rural settlements, and cultivated land in mountainous areas in the upper reaches of the Min River by analyzing geohazards data, settlements data and cultivated land data. Geohazards change the landform and provide material basis and space for the occurrence and development of cultivated land and settlements. However, human production and life are not only stressed by geohazards, but also one of the main factors inducing geohazards. The Settlements in the upper reaches of the Min River can be categorized into production-stressed settlements and life-stressed settlements. With the transformation of the social economy and society's attention to the ecological function of the region, geohazards risk management of life-stressed settlements is of more importance. The "two-wheel-drive" strategy of new urbanization and rural revitalization provides opportunities for rural development in mountainous areas and also changes the role of land in human-land relationships. To fully consider natural capital in the sustainable livelihoods of farmers, it is necessary to evaluate the risk degree of geohazards in settlements at the small catchment scale and improving the external connectivity of the settlements, which is the key for promoting the optimization of natural environmental assets in these mountain settlements.